METHODOLOGICAL BASIS OF TEACHING THE SUBJECT OF MODERN HISTORY OF UZBEKISTAN (American Journal of Research in Humanities and Social Sciences, 2024)
This article discusses the methodological foundations of teaching the subject of the latest history of Uzbekistan. The author, relying on scientific data and existing literature, studied and analyzed the specific aspects of the methodological foundations of teaching the subject of the latest history of Uzbekistan.